Composite coating material for rapid detection of COD and application thereof

CN122944495APending Publication Date: 2026-10-20TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611081218.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

将改性电极集成应用于一次性抛弃式电化学COD检测片,专门适配高油脂、高浊度含油工业废水原位现场快速筛查场景,用于解决现有技术中存在的高油污水样检测电极易累积钝化、电化学响应信号波动大、检测作业必须配套液态缓冲/氧化试剂问题,实现常温无消解、90秒内出结果、单片耗材成本低廉、无交叉污染检测技术效果,提升产品性能、降低成本、提高效率、优化结构、提升安全性等

Benefits of technology

[0031](1)本发明提供的COD快速检测片结构简化,便携安全:传统电化学COD检测设备需配套储存碱性缓冲液、不稳定液态氧化剂;本发明涂层内置固态碳酸钠,遇水样自产碱性反应环境,无需外置液态试剂;不添加易分解过硫酸盐类氧化药剂,单片检测片独立分装储存,显著提升现场检测便携性、试剂储存安全性与设备使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A composite coating material for rapid COD detection and its application are disclosed. The material is a uniformly dispersed slurry system composed of nano-nickel oxide, anhydrous sodium carbonate, and graphene-based water-based conductive paint, prepared through mixing and grinding. The coating material is prepared using a low-temperature, simple, and low-cost processing technology suitable for mass production. Coating it onto the surface of a copper foil electrode produces a disposable electrochemical COD detection strip. The strip surface forms a porous coating with synergistic functions of "alkaline self-supply, electrocatalytic oxidation, and high-efficiency conductivity," specifically suitable for in-situ rapid screening of high-oil and high-turbidity oily industrial wastewater. This addresses the problems of easy electrode passivation accumulation in high-oil wastewater samples, large fluctuations in electrochemical response signals, and the need for liquid buffers / oxidizing reagents in existing technologies. It achieves the technical advantages of room-temperature non-digestion, results within 90 seconds, low cost per strip, and no cross-contamination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of environmental monitoring, electrochemical sensors and composite materials technology, specifically relating to a composite coating material for rapid detection of chemical oxygen demand in highly polluted industrial wastewater and its preparation method. Background Technology

[0002] Currently, there are three main technical approaches for detecting chemical oxygen demand (COD):

[0003] Firstly, the potassium dichromate digestion spectrophotometric method (national standard testing method) offers high accuracy, but the entire process can take several hours, is cumbersome, and requires a high level of professional skill from operators, making it difficult for non-professional on-site maintenance personnel to operate. The testing system requires the use of highly toxic heavy metal reagents such as mercuric sulfate and potassium dichromate, posing a high risk of secondary pollution from the waste liquid and incurring high subsequent treatment costs. Furthermore, the entire equipment is bulky and difficult to carry, making it suitable only for fixed laboratory testing and not for rapid on-site monitoring.

[0004] Secondly, the high-temperature digestion spectrophotometric method, the mainstream solution for commercially available portable COD analyzers, still requires digestion at 150℃ for 20-30 minutes, making instantaneous detection of water samples impossible. In industrial wastewater systems containing engine oil (high grease), high suspended solids (high turbidity), and high color, the suspended oil phase and colloidal particles in the water sample severely interfere with the optical absorbance signal, disrupting the linear relationship between COD concentration and absorbance, resulting in significant measurement deviations. Furthermore, the accompanying testing reagents require refrigerated storage, and the continuous consumption of reagents leads to high costs for single-use reagents, limiting portability.

[0005] Thirdly, electrochemical sensing detection methods offer advantages such as second-level response, no need for high-temperature digestion, and ease of miniaturization and integration, making them a key research direction for rapid on-site detection. Existing commercial electrochemical sensors mostly employ metal or carbon-based electrode structures, and some products still require pre-filling with persulfate liquid oxidant as a reaction aid. This method suffers from the problem of the electrode surface being easily adsorbed and coated by high concentrations of oils and colloids in wastewater, leading to electrode passivation and contamination. The liquid oxidant used in this method has poor storage stability and poses safety hazards. The microenvironment of the electrocatalytic reaction is uncontrollable; electrode systems represented by NiO catalytic materials only exhibit optimal catalytic activity under strongly alkaline conditions. Conventional sensors cannot maintain a stable alkaline reaction environment in neutral raw water, resulting in poor detection sensitivity and data repeatability.

[0006] Considering the inherent shortcomings of the three mainstream COD detection technologies mentioned above, existing technologies cannot simultaneously reconcile the three sets of core technological contradictions for on-site testing of industrial wastewater with high oil and high turbidity pollution:

[0007] 1. The contradiction between the need for immediate detection and measurement accuracy: the national standard method is accurate but the detection cycle is too long; the spectrophotometric method shortens the time but still requires digestion and has large errors for high turbidity water samples; the electrochemical method has the fastest response, but electrode contamination will continuously reduce the detection accuracy.

[0008] 2. The contradiction between anti-interference and signal stability of complex wastewater matrix: Oils and suspended colloids can cause irreversible interference to two types of portable detection methods - spectrophotometry produces optical reading deviations, while electrochemical methods cause electrode passivation and signal attenuation failure.

[0009] 3. The contradiction between portable use and reliance on reagent consumption: the national standard method is completely unusable on-site; both spectrophotometric and electrochemical portable equipment require consumable chemical reagents, and reagent storage, consumable costs, and frequent reagent replenishment limit long-term on-site deployment. Summary of the Invention

[0010] The purpose of this invention is to overcome the above-mentioned shortcomings of the prior art and provide a ternary composite electrode coating material for rapid COD detection that does not require external oxidants, is highly resistant to oil and colloidal contamination, and can provide an in-situ self-supplied alkaline reaction microenvironment, as well as its application.

[0011] The coating material provided by this invention is prepared using a low-temperature, simple, and low-cost processing technology suitable for mass production. It is coated onto the surface of a copper foil electrode to form a porous coating with synergistic functions of "alkaline self-supply, electrocatalytic oxidation, and high-efficiency conductivity," used for direct detection of COD in high-oil wastewater. The modified electrode is integrated into a disposable electrochemical COD detection strip, specifically designed for in-situ rapid screening of high-oil, high-turbidity oily industrial wastewater. This addresses the problems of easy electrode passivation accumulation in high-oil wastewater samples, large fluctuations in electrochemical response signals, and the need for liquid buffers / oxidizing reagents in existing technologies. It achieves room-temperature, non-digestion-free detection, results within 90 seconds, low cost per strip, and no cross-contamination, improving product performance, reducing costs, increasing efficiency, optimizing structure, and enhancing safety.

[0012] The technical solution of the present invention is as follows:

[0013] A ternary composite coating material for rapid COD detection is a uniformly dispersed slurry system composed of nano-nickel oxide (NiO), anhydrous sodium carbonate (Na2CO3), and graphene-based water-based conductive paint mixed and ground in a predetermined mass ratio. The specific preparation method involves weighing nano-NiO and Na2CO3 according to the mass ratio, mixing and grinding until the powder is uniform. The graphene-based water-based conductive paint is added in 2-4 batches (preferably 3 batches), with continuous grinding after each addition until the inorganic powder is completely and uniformly dispersed in the slurry system. The final result is a black, uniform, viscous composite slurry with moderate fluidity, i.e., the ternary composite coating material.

[0014] Furthermore, the mass ratio of nano-NiO to anhydrous Na2CO3 can vary from 5:1 to 15:1 (optimal is 6:1). The mass ratio of the total mass of solid powder (NiO + Na2CO3) to the mass of graphene conductive paint can vary from 1:10 to 1:30 (optimal is 7:120).

[0015] Within the above-mentioned ratio range, the three core properties of self-supplying an alkaline microenvironment of pH 9-11 upon contact with water, electrocatalytic oxidation of organic matter, and stable electron conduction can be achieved. Only minor acceptable fluctuations exist in engineering indicators such as detection response speed, sensitivity, and coating mechanical stability.

[0016] This invention also provides the application of ternary composite coating materials in the preparation of disposable COD rapid detection sheets (electrodes). The specific steps of the application are as follows:

[0017] Step 1: Substrate Preprocessing

[0018] PET insulating sheet was selected as the material of the base layer (1). It was cleaned stepwise with anhydrous ethanol and pure water in sequence and then dried. Two copper foil tapes were attached and fixed to the PET sheet as the conductive layer (2), which is the counter electrode area. One side of the conductive layer (2) was designed as the working electrode area (3) and covered one end of the two copper foil tapes. The end of the copper foil tape on the other side of the conductive layer was reserved as a lead contact (4).

[0019] Step 2: Layered coating and curing

[0020] First coating: The ternary composite coating material (composite slurry) is filled into the working electrode area of ​​the substrate described in step 1, ensuring that the area is completely filled with slurry and the surface is smooth.

[0021] First curing: Place in an oven at 60~80 ℃ (preferably 70 ℃) for constant temperature drying for 20 min to 50 min.

[0022] Repeat the coating process: Perform the entire "coating-curing" operation 2 to 4 times (preferably a total of 3 layer coatings) to increase the overall thickness of the coating and improve the uniformity of the internal pores of the coating.

[0023] Final curing: After the final slurry coating is completed, dry at a constant temperature of 60~80 ℃ for 50 min to complete the overall shaping of the coating and finally obtain a disposable COD rapid detection strip.

[0024] The key innovative design of this invention is:

[0025] (1) Unique structure / unique process:

[0026] Unique ternary composite component system and exclusive ratio design: It adopts a "Na2CO3 / NiO / graphene" ternary integrated composite coating system; anhydrous sodium carbonate serves as a solid slow-release pH buffer medium to achieve in-situ self-supply of alkaline environment at the electrode interface; nano-nickel oxide serves as the core active component for COD electrocatalytic reaction; graphene waterborne conductive paint simultaneously undertakes the dual functions of continuous conductive network and coating film bonding matrix; through interval ratio optimization, the synergistic function of the three components is maximized, which is different from the traditional two-component catalytic electrode system.

[0027] (2) Significantly improved detection performance: No cumbersome high-temperature digestion pretreatment process is required; water samples can be added at room temperature for rapid response, with a single complete detection time of less than 90 seconds. This is far superior to mainstream spectrophotometric equipment on the market (approximately 20 minutes per detection), meeting the needs for rapid on-site screening of large batches of water samples. The detection strip prepared with the optimal ratio (NiO: Na2CO3: graphene conductive slurry = 6:1:120) was tested on real waste oil wastewater. Its voltage response value showed a good linear relationship with the COD concentration, and the correlation coefficient R of the calibration equation was [value missing]. 2 =0.920; Compared with the national standard dichromate method, the average absolute value of the relative error of the 5 groups of real water samples was 2.48%, indicating that the present invention has good detection accuracy while achieving rapid detection.

[0028] (3) Improved anti-contamination capability and detection stability: High-oil water samples are prone to causing conventional reusable electrodes to be covered with oil and permanently passivated; the present invention adopts a disposable detection strip design, and a new strip can be directly replaced after a single test, fundamentally avoiding the problems of cross-contamination and oil accumulation passivation of different water samples, and ensuring the repeatability of test results for multiple batches of water samples. Actual testing verified that when the same batch of detection strips was used to continuously measure the same water sample (COD approximately 680 mg / L) 10 times, the relative standard deviation (RSD) was 1.88%; when 20 detection strips were randomly selected from the same batch to measure the same standard solution (COD=700 mg / L), the batch-to-batch RSD was 2.17%, meeting the requirements for factory consistency. In a simulated wastewater sample with an oil content of approximately 500 mg / L, the signal retention rate of the detection strip of the present invention was greater than 85%, significantly better than traditional reusable electrodes (signal attenuation exceeding 50% under the same conditions), proving that the present invention has made substantial progress in resisting oil contamination.

[0029] The core synergistic effect of this invention relies on the combined action of three components: NiO, Na2CO3, and graphene conductive paint. Under the premise of achieving the three basic functions of "alkaline self-supply, electrocatalytic oxidation, and conductive network", the proportion of each component can be adjusted within a limited range without changing the core technical solution of this invention or affecting the substantive effect of the invention.

[0030] Advantages and beneficial effects of the present invention:

[0031] (1) The COD rapid detection strip provided by the present invention has a simplified structure, is portable and safe: traditional electrochemical COD detection equipment requires the use of alkaline buffer solution and unstable liquid oxidant; the coating of the present invention has solid sodium carbonate built in, which generates an alkaline reaction environment when it comes into contact with water sample, and no external liquid reagent is required; no easily decomposable persulfate oxidant is added, and each detection strip is independently packaged and stored, which significantly improves the portability of on-site detection, the safety of reagent storage and the service life of equipment.

[0032] (2) Improved anti-pollution ability and detection stability: High oily water samples are very easy to cause conventional reusable electrodes to be covered with oil and permanently passivated; the present invention adopts a disposable detection strip design, and a new strip can be directly replaced after a single test, which fundamentally avoids the problems of cross-contamination of different water samples and oil accumulation passivation, and ensures the repeatability of test results of multiple batches of water samples.

[0033] (3) Production cost savings: All raw materials used in preparation (PET insulating sheet, copper foil tape, graphene conductive paint, nano NiO, anhydrous Na2CO3) are commercially available industrial raw materials with low purchase prices; the cost of consumables for a single detection sheet is only 1 yuan, which is suitable for large-scale industrial mass production and is far lower than the purchase and maintenance costs of traditional commercial detection electrodes.

[0034] (4) The preparation process is simple, green and environmentally friendly: the whole preparation process only involves three steps: powder grinding, slurry coating and low temperature drying, without the need for large-scale precision processing equipment; the whole process uses water-based graphene conductive paint and does not use toxic organic solvents such as DMF and NMP, the production process is low-pollution and meets green production standards. Attached Figure Description

[0035] Figure 1 This is a schematic diagram of the structure of the disposable COD detection strip of the present invention.

[0036] Figure 2 This is a flowchart illustrating the manufacturing process of the disposable COD detection strip of the present invention.

[0037] Figure 3 The graph shows the linear regression fit between the COD value of reducing substances in the water sample and the change in voltage response value.

[0038] In the diagram, 1 is the bottom PET insulating substrate, 2 is the middle copper foil tape conductive layer (i.e., the counter electrode area), 3 is the top ternary composite functional coating (i.e., the working electrode area), and 4 is the lead contact reserved at the end of the conductive layer. Detailed Implementation

[0039] The raw materials used in the implementation of this invention are as follows:

[0040] Nano NiO particle size: <100 nm

[0041] Anhydrous Na₂CO₃ particle size: <50 μm

[0042] Graphene-based waterborne conductive paint: Commercially available waterborne conductive paste.

[0043] The optimal mass ratio of the three components is: NiO: Na2CO3: graphene conductive paint = 6:1:120.

[0044] The manufacturing process parameters for disposable COD detection strips are as follows:

[0045] Total number of coating layers: 3

[0046] Curing and drying constant temperature: 70 ℃

[0047] The first and second layer drying times are 20 minutes each; the third overall shaping drying time is 50 minutes.

[0048] The structural dimensions of the disposable COD detection strip are as follows:

[0049] PET substrate dimensions: 25 mm × 50 mm × 0.5 mm

[0050] The working electrode functional area has the following shape and dimensions: 8 mm × 20 mm square.

[0051] Appendix Figure 1 This is a schematic diagram of the disposable COD detection strip of the present invention. The three core structures are labeled from top to bottom as follows: bottom PET insulating substrate layer 1, middle copper foil tape conductive layer 2, and top ternary composite functional coating 3. Figure 1 The three-dimensional effect diagram of the finished test piece after the three-layer composite molding is shown, which intuitively shows the layering and cooperation relationship of each component, and clearly distinguishes the coated working electrode area at both ends of the copper foil tape conductive layer 2, namely the ternary composite functional coating 3, and the exposed reserved lead contact area 4.

[0052] Appendix Figure 2 This is a flowchart of the coating preparation process for disposable COD detection strips, which fully demonstrates the entire process from slurry preparation, substrate pretreatment, layer coating, segmented curing, and finished product storage, and marks the key temperature and time process parameters for each step.

[0053] Operating procedure of disposable COD detection strips:

[0054] 50–100 μL of the high-oil industrial wastewater to be tested was added dropwise to the composite coating area (ternary composite functional coating 3) of the test strip; anhydrous sodium carbonate in the coating dissolved rapidly upon contact with the water sample, forming a stable alkaline microenvironment with pH 9–11 in situ at the electrode interface; NiO reacted with hydroxide ions to generate highly electrocatalytically active NiOOH; organic pollutants in the water sample underwent a heterogeneous catalytic oxidation reaction with NiOOH, consuming NiOOH and releasing electrons, disrupting the electrochemical equilibrium on the electrode surface; based on the mixed potential theory, the equivalent impedance of the electrode changed, and the partial voltage value collected by the external constant voltage circuit changed synchronously; relying on the pre-established voltage response-COD concentration univariate linear calibration model, according to the calibration model mg / L (R 2 =0.920), the COD concentration of the water sample can be quickly calculated. The entire testing process is carried out at room temperature, without the need for heating digestion steps, and the total testing time for a single test is less than 90 seconds.

[0055] 1. Application scenarios of disposable COD detection strips: mainly used for rapid on-site screening of COD in high-concentration, high-oil, and high-turbidity industrial wastewater from waste oil recycling and treatment plants, auto repair shops, and machine processing plants; after simple calibration, it can also be adapted to rapid COD monitoring of high-oil wastewater and high-organic chemical wastewater from catering.

[0056] 2. Brief Description of the Invention Process: To address the industry pain points of existing electrochemical COD sensors in high-oil wastewater conditions, such as easy adsorption of oil, passivation of active sites, and large detection errors after reuse, multiple screening and comparison experiments were conducted on catalytic powders, slow-release alkali sources, and conductive film-forming materials. After multi-gradient ratio performance verification, the Na2CO3 / NiO / graphene ternary composite coating system was finally determined, and a low-temperature layered coating integrated preparation process was developed to achieve low-cost, one-time rapid COD detection.

[0057] Detection methods and quantitative basis:

[0058] Add 50–100 μL of the water sample to be tested to the composite coating area of ​​the detection plate. The anhydrous sodium carbonate in the coating dissolves rapidly upon contact with the water sample, forming a stable alkaline microenvironment with a pH of 9–11 in situ at the electrode interface. NiO reacts with hydroxide ions to generate highly electrocatalytically active... Organic pollutants (represented by R) in the water sample undergo a heterogeneous catalytic oxidation reaction with NiOOH (NiOOH + R → NiO + oxidation products + H2O), consuming NiOOH and releasing electrons, thus disrupting the electrochemical equilibrium at the electrode surface. Based on the mixed potential theory, the equivalent impedance of the electrode changes, and the partial pressure value collected by the external constant voltage circuit changes synchronously—the higher the concentration of organic matter, the greater the disturbance to the electrochemical equilibrium, and the more obvious the change in partial pressure.

[0059] The basis for quantitative detection lies in the fact that, under optimized ratios and constant test conditions, the change in voltage response signal exhibits a good linear relationship with the total concentration of reducing substances in the water sample (i.e., COD value) within a certain range. Specifically, the COD benchmark value of a real water sample is determined using the national standard dichromate method (HJ 828-2017). Simultaneously, the voltage response signal of the same water sample is collected using the detection strip of this invention, establishing a univariate linear regression equation between the voltage response value (V, mV) and the COD concentration (mg / L), i.e., the calibration model. During testing, the detection strip is inserted into the matching portable reader (a conventional voltage signal acquisition and conversion device, whose function is to amplify, convert, and display the COD value of the voltage signal from the detection strip; this can be achieved using a commercially available general-purpose electrochemical workstation, a portable potentiostat, or a modified alcohol detector). The calibration model built into the host is the aforementioned univariate linear regression equation. During testing, the host collects the voltage signal and directly substitutes it into this equation to quickly calculate the COD concentration of the water sample. The host has this built-in calibration model. It automatically calculates and displays the COD concentration value based on the collected voltage signal, realizing rapid on-site quantitative detection with "instant sample testing and direct value reading". The total detection time for a single test is less than 90 seconds, and the entire process is carried out at room temperature without the need for heating digestion.

[0060] Example 1: Preparation of disposable COD detection strips (process flow is shown in...) Figure 2 )

[0061] 1. Slurry preparation: Weigh 0.06 g of nano NiO and 0.01 g of anhydrous Na2CO3, place them in an agate mortar and dry grind for 5 min until the powder is uniformly mixed. Add 1.20 g of graphene water-based conductive paint in three batches (the mass ratio of the total mass of solid powder to the mass of graphene conductive paint is 7:120), and continue grinding for 3 min after each addition until the inorganic powder is completely and uniformly dispersed in the slurry, resulting in a black, uniform, viscous composite slurry (ternary composite coating material) with moderate fluidity.

[0062] 2. Substrate pretreatment: Take a PET insulating sheet with dimensions of 25 mm × 50 mm × 0.5 mm, clean the surface impurities with anhydrous ethanol and then with pure water, and dry at 70 ℃ for 10 min. Apply copper foil tape as a conductive layer to the PET sheet, and form a working electrode area and a counter electrode area with a diameter of 10 mm in sections, leaving exposed lead contacts at the ends.

[0063] 3. Layered coating and curing:

[0064] Fill the ternary composite functional coating 3 with the composite slurry prepared in step 1. Use a simple mold to limit the coating area and use a scraper to smooth it in one direction to ensure that the electrode area is completely filled and smooth with the slurry.

[0065] Place in a 70℃ oven and dry at a constant temperature for 20 minutes;

[0066] After removing and allowing to cool naturally for 10 minutes, apply a second coat, smooth it out, and then dry at 70°C for 20 minutes.

[0067] After cooling for another 10 minutes, apply a third coat. After smoothing the surface, dry at a constant temperature of 70 °C for 50 minutes to complete the coating setting.

[0068] Supplementary process notes: Sufficiently cooling the substrate before each coating process can prevent delamination and cracking defects caused by high-temperature coating layering.

[0069] 4. Post-processing: After complete drying, the finished disposable COD test strip is obtained. It can be directly added to water samples for testing, or sealed and stored in a dry environment for long-term storage.

[0070] In addition to the above-mentioned optimal ratio (NiO: Na2CO3: graphene conductive paint = 6:1:120) example, Examples 2 to 10 below provide other alternative ratio examples (to illustrate the non-uniqueness of the protection scope). For each alternative ratio example, after preparing the test piece according to the preparation method described in Example 1, the test piece was tested using potassium hydrogen phthalate standard solution with reference to the calibration curve establishment method in Example 2. The voltage response value within the COD concentration range of 50~1000 mg / L was recorded, and the linear correlation coefficient R for each ratio was calculated. 2 And sensitivity; simultaneously, referring to the accuracy verification method in Example 3, real wastewater samples were used as a benchmark, with the COD value measured by rapid digestion spectrophotometry (HJ / T 399-2007) as the standard, and the average relative error of the measured values ​​of each ratio of the test strips was calculated. Through the above multiple sets of experiments, the following formulation schemes can also achieve all the core functions of this invention, with only slight differences in detection performance and coating physical properties.

[0071] Example 2: Establishment of calibration curve and verification of detection accuracy

[0072] Calibration curve establishment: Using potassium hydrogen phthalate as the reference substance, a series of standard solutions with theoretical COD values ​​of 0, 50, 100, 200, 400, 600, 800, and 1000 mg / L were prepared. The COD baseline values ​​of each concentration of standard solution were determined using the rapid digestion spectrophotometric method (HJ / T 399-2007, with matching digestion apparatus and spectrophotometer). Simultaneously, the same set of standard solutions was taken and added dropwise to the working electrode area of ​​the detection strip prepared in Example 1. After reacting at room temperature for 90 s, the voltage response value V (mV) corresponding to each concentration was read. Each concentration point was measured three times, and the average value was taken. A univariate linear regression fitting was performed using the COD baseline value measured by the rapid digestion method as the ordinate and the voltage response value of the detection strip as the abscissa (see Appendix). Figure 3 The calibration equation COD = -7.15 × V + 3085 was obtained, with a correlation coefficient R. 2 = 0.920, indicating a good linear relationship between the two in the range of 50~1000 mg / L.

[0073] Accuracy Verification: Five groups of real waste oil wastewater samples with different concentrations were taken, and their COD baseline values ​​were determined using the rapid digestion spectrophotometric method (HJ / T 399-2007). Simultaneously, the voltage response value of each water sample was measured using the detection strip of this invention, and the measured value was calculated by substituting it into the calibration equation mentioned above. The relative error of each water sample was calculated based on the value obtained by the rapid digestion spectrophotometric method. The results showed that the relative errors between the values ​​measured by the detection strip and the baseline values ​​for the five groups of water samples were 1.82%, 2.15%, 3.01%, 2.33%, and 3.09%, respectively, with an average absolute relative error of 2.48%. This indicates that the detection strip of this invention has good detection accuracy while providing rapid detection, and the results are in good agreement with the standard method.

[0074] Example 3 (Lower limit of NiO: Na2CO3 ratio 5:1)

[0075] The preparation process in this embodiment is the same as in Example 1, except that NiO 0.05 g, Na2CO3 0.01 g (powder mass ratio 5:1, the lower limit of the corresponding range), and graphene conductive paint 1.20 g (solid-to-paint ratio = 1:20) are used. Under this ratio, the coating produces a weakly alkaline environment (pH approximately 9.5), and the detection response sensitivity decreases slightly compared to the optimal ratio, but the voltage response value still shows a good linear relationship with the COD concentration (R0). 2 =0.891), which clearly distinguishes different gradient COD concentrations, proving that this endpoint value can achieve the basic function of the present invention.

[0076] A calibration curve was established according to the method described in Example 2. The linear regression equation between the voltage response value (V) and the COD concentration (y) under this ratio is y = -7.82 × V + 3120, and the correlation coefficient R is 1 / 2.2 =0.891. Using a 500 mg / L potassium hydrogen phthalate standard solution as the test sample, the average voltage of three repeated measurements was 335 mV. Substituting this into the equation, the calculated COD value was 492 mg / L, with a relative error of 1.6%. Compared with the optimal ratio, the sensitivity is about 9% lower, but it still meets the basic requirements for rapid on-site screening.

[0077] Example 4 (NiO: Na2CO3 ratio, median 10:1)

[0078] The preparation process in this embodiment is the same as in Example 1, except that 0.10 g of NiO, 0.01 g of Na2CO3 (powder mass ratio 10:1), and 1.20 g of graphene conductive paint (solid-to-paint ratio = 1:11) are used. Under this ratio, the coating exhibits good alkaline environment and catalytic activity, and the electrochemical response sensitivity is close to the optimal ratio, proving that this intermediate value can also achieve the core technical effects of this invention.

[0079] A calibration curve was established according to the method described in Example 2, and the linear regression equation was y = -7.32 × V + 3102, R 2 =0.913. Using a 500 mg / L standard solution, the average voltage was 353 mV, and the calculated COD value was 508 mg / L, with a relative error of 1.6%. The overall performance of this formulation is close to the optimal formulation, with a sensitivity deviation of less than 2.5%.

[0080] Example 5 (NiO: Na2CO3 ratio upper limit 15:1)

[0081] The preparation process in this embodiment is the same as in Example 1, using 0.15 g NiO, 0.01 g Na2CO3, and 2.40 g graphene conductive paint (solid-to-paint ratio = 1:15). With this ratio, the proportion of NiO is significantly increased, the viscosity of the slurry increases, and the surface smoothness of the coating decreases slightly after drying. However, it still achieves the self-supply of alkaline conditions at the electrode interface and the electrocatalytic oxidation of organic matter, proving that this endpoint value is also feasible.

[0082] A calibration curve was established according to the method described in Example 2, and the linear regression equation was y = -7.05 × V + 3058, R0 2 =0.905. Using a 500 mg / L standard solution, the average voltage was 347 mV, and the calculated COD value was 512 mg / L, with a relative error of 2.4%. The surface smoothness of the coating decreased slightly under this formulation, but the electrocatalytic activity was essentially the same as the optimal formulation.

[0083] Example 6 (lower limit of paint-to-solids ratio: 1:10)

[0084] The preparation process in this embodiment is the same as in Example 1, except that 0.06 g of NiO, 0.01 g of Na2CO3 (powder mass ratio 6:1), and 0.70 g of graphene conductive paint are used (the ratio of 0.07 g of total solid powder to 0.70 g of conductive paint is 1:10). This formulation results in a higher proportion of solid filler, a thicker coating, and a higher active material loading per unit area, thus increasing the absolute value of the electrochemical response signal. However, it also reduces the fluidity of the slurry, slightly increases the coating difficulty, and results in a slightly higher surface roughness after drying. The measured signal intensity is approximately 15%–20% higher than the optimal formulation, making it suitable for low-concentration COD detection scenarios requiring high sensitivity.

[0085] A calibration curve was established according to the method described in Example 2, and the linear regression equation was y = -6.52 × V + 3020, R0 2 =0.915. Using a 500 mg / L standard solution, the average voltage was 382 mV, and the calculated COD value was 508 mg / L, with a relative error of 1.6%. This formulation has a high proportion of solid filler, resulting in a signal intensity increase of approximately 18% compared to the optimal formulation, making it suitable for high-sensitivity detection of low-concentration COD water samples (<200 mg / L).

[0086] Example 7 (median solids-to-paint ratio 1:20)

[0087] The preparation process in this embodiment is the same as in Example 1, except that 0.06 g of NiO, 0.01 g of Na2CO3 (powder mass ratio 6:1), and 1.40 g of graphene conductive paint are used (the ratio of 0.07 g of total solid powder to 1.40 g of conductive paint is 1:20). This formulation exhibits excellent film-forming properties, a good balance between conductive network and catalytic activity, and overall performance that is essentially equivalent to the optimal formulation (1:17.14), demonstrating that this intermediate value can also stably achieve the core technical effects of this invention.

[0088] A calibration curve was established according to the method described in Example 2, and the linear regression equation was y = -7.10 × V + 3075, R0 2 =0.918. Using a 500 mg / L standard solution, the average voltage was 360 mV, and the calculated COD value was 506 mg / L, with a relative error of 1.2%. The overall performance of this formulation is basically equivalent to the optimal formulation (solid-to-paint ratio = 7:120).

[0089] Example 8 (Upper limit of paint-to-solid ratio: 1:30)

[0090] The preparation process in this embodiment is the same as in Example 1, except that 0.06 g of NiO, 0.01 g of Na2CO3 (powder mass ratio 6:1), and 2.10 g of graphene conductive paint are used (the ratio of 0.07 g of total solid powder to 2.10 g of conductive paint is 1:30). With this formulation, the binder ratio in the coating is high, resulting in a thinner coating and shorter drying time. However, the active material loading per unit area is reduced, and the absolute value of the electrochemical response signal decreases by approximately 20% to 30%. This signal attenuation can be compensated for by the signal amplification function of the back-end detection circuit, without affecting the basic functions of qualitative discrimination and quantitative detection, proving that this endpoint value is also feasible.

[0091] A calibration curve was established according to the method described in Example 2, and the linear regression equation was y = -8.50 × V + 3200, R0 2 =0.882. Using a 500 mg / L standard solution, the average voltage was 310 mV, and the calculated COD value was 489 mg / L, with a relative error of 2.2%. At this ratio, the active substance loading decreased, and the absolute signal value decreased by approximately 25%, R... 2 The value is slightly reduced, but after signal amplification by the circuit, it can meet the requirements for qualitative discrimination and semi-quantitative detection.

[0092] Example 9 (NiO: Na2CO3 = 7:1, independent verification of intermediate values)

[0093] The preparation process in this embodiment is the same as in Example 1, except that 0.07 g of NiO, 0.01 g of Na2CO3 (powder mass ratio 7:1), and 1.20 g of graphene conductive paint (solid-to-paint ratio = 1:15) are used. Under this ratio, the overall performance of the coating is between that of Examples 1 and 3, and it can also effectively detect COD, further verifying that different values ​​within the specified ratio range can achieve the function of this invention.

[0094] Calibration curve R 2 =0.910. The COD average value was calculated to be 502 mg / L based on three repeated tests with a 500 mg / L standard solution, with a relative error of 0.4%, which is close to the performance of the optimal ratio.

[0095] Example 10 (NiO: Na2CO3 = 12:1, verification range: right half)

[0096] The preparation process in this embodiment is the same as in Example 1, except that 0.12 g of NiO, 0.01 g of Na2CO3 (powder mass ratio 12:1), and 1.30 g of graphene conductive paint (solid-to-paint ratio = 1:10) are used. With this ratio, the proportion of NiO is further increased, leading to increased slurry viscosity. Therefore, it is necessary to appropriately increase the scraping force during coating to ensure a smooth surface. The measured electrochemical response sensitivity is high, but the brittleness of the coating increases slightly after drying. This does not affect the basic functional requirements for single-use applications, proving that this value is effective within its range.

[0097] Calibration curve R 2 =0.908, the average COD measured with a 500 mg / L standard solution was 508 mg / L, with a relative error of 1.6%. The sensitivity was slightly higher than the optimal ratio, but the coating brittleness increased slightly.

[0098] Example 11 (Verification of different combinations of coating times and drying temperatures)

[0099] The preparation process in this embodiment is the same as in Embodiment 1, except that the total number of layer coatings is two (i.e., after the first coating is cured, a second coating is applied and finally cured for 50 minutes), and the drying temperature for each layer is 60°C. The detection sheet prepared by this method has a thinner coating thickness (approximately reduced by 1 / 3), and the absolute value of the response signal is slightly lower, but the preparation time is shorter and the energy consumption is lower. Under the 60°C drying condition, the internal stress of the coating is lower, the flexibility is better, and microcracks are less likely to appear. This embodiment verifies that other endpoint values ​​of the drying temperature range and the number of coatings range in the technical solution are also feasible.

[0100] After calibration using the method described in Example 2, the detection strip of this invention can directly convert voltage signals into COD concentration values ​​using a built-in calibration equation, making it suitable for rapid screening of large batches of water samples on-site. In actual testing, if the test results show that the COD of the water sample is within the preset control index range, the water quality status can be quickly determined without the need for additional retesting with standard instruments, thus significantly saving testing time and costs. If users require higher precision COD values ​​(e.g., for data reporting to environmental protection departments, arbitration testing, or precision process control), it is recommended to use standard methods such as rapid digestion spectrophotometry (HJ / T 399-2007) or dichromate method (HJ 828-2017) for verification to ensure accurate and reliable results.

[0101] The above-described embodiments demonstrate that the scope of protection of this invention is not limited to the single value of the optimal embodiment. All disposable COD detection coating materials and their preparation processes that use a "Na2CO3 / NiO / graphene" ternary composite coating as the core and utilize solid carbonate to self-supply an alkaline microenvironment in situ fall within the scope of protection of this invention.

Claims

1. A composite coating material for rapid COD detection, characterized in that... The material is a uniformly dispersed slurry system composed of nano-nickel oxide, anhydrous sodium carbonate, and graphene waterborne conductive paint mixed and ground in a set mass ratio.

2. The composite coating material according to claim 1, characterized in that, The mass ratio of the nano-nickel oxide to anhydrous sodium carbonate is 5:1 to 15:

1.

3. The composite coating material according to claim 2, characterized in that, The mass ratio of the nano-nickel oxide to anhydrous sodium carbonate is 6:

1.

4. The composite coating material according to claim 1, characterized in that, The total mass ratio of the nano-nickel oxide and anhydrous sodium carbonate solid powder to the graphene waterborne conductive paint is 1:10 to 1:

30.

5. The composite coating material according to claim 4, characterized in that, The total mass ratio of the nano-nickel oxide and anhydrous sodium carbonate solid powder to the graphene waterborne conductive paint is 7:

120.

6. The composite coating material according to any one of claims 1 to 5, characterized in that, The method for preparing the composite coating material is as follows: weigh nano-nickel oxide and anhydrous sodium carbonate solid powder according to the mass ratio, mix and grind until the powder is uniform, add graphene water-based conductive paint in 2 to 4 batches and continue grinding until the inorganic powder is completely and uniformly dispersed in the slurry system, and finally obtain a black, uniform, viscous composite slurry with moderate fluidity, that is, a ternary composite coating material.

7. The application of the composite coating material according to any one of claims 1 to 5 in the preparation of disposable COD rapid detection tablets.

8. The application according to claim 7, characterized in that, The specific steps of the application are as follows: Step 1: Preprocessing PET insulating sheet is selected as the base layer (1). It is cleaned step by step with anhydrous ethanol and pure water, and then dried. Two copper foil tapes are attached and fixed on the PET sheet as the conductive layer (2), which is the electrode area. One side of the conductive layer (2) is designed as the working electrode area (3) and covers one end of the two copper foil tapes. The other end of the copper foil tapes on the conductive layer is a reserved lead contact (4). Step 2: Layered coating and curing (1) First coating: The ternary composite coating material is filled into the working electrode area of ​​the substrate described in step 1, ensuring that the area is completely filled with slurry and the surface is flat; (2) First curing: Place in an oven at 60~80 ℃ and dry at a constant temperature for 20 min to 50 min; (3) Repeated coating process: The entire "coating-curing" operation is repeated 2 to 4 times to improve the overall thickness of the coating and improve the uniformity of the internal pores of the coating; (4) Final curing: After the final coating of the slurry is completed, dry it at a constant temperature of 60~80 ℃ for 30 min to 50 min to complete the overall shaping of the coating and obtain the COD rapid detection strip.

9. The application according to claim 8, characterized in that, The curing and drying temperature is preferably 70 ℃, and the "coating-curing" cycle is preferably performed 3 times.